1998
DOI: 10.1164/ajrccm.158.3.9710007
|View full text |Cite
|
Sign up to set email alerts
|

Angiotensin-converting Enzyme Inhibition Delays Pulmonary Vascular Neointimal Formation

Abstract: Primary pulmonary hypertension (PPH) is a disease characterized pathologically by pulmonary artery medial hypertrophy, adventitial thickening, and neointimal proliferation. Increasing recognition of the importance of remodeling to the pathogenesis of PPH suggests new therapeutic possibilities, but it will be necessary to (1) identify essential mediators of remodeling, and (2) demonstrate that inhibiting those mediators suppresses remodeling before new antiremodeling therapies can be considered feasible. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
47
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(51 citation statements)
references
References 66 publications
(43 reference statements)
4
47
0
Order By: Relevance
“…The death rate from failing myocardium in the right ventricle as a result of MCT administration increases in a dose-dependent manner. [12][13][14][15][16][17] Hirota, et al 2) subcutaneously injected 40 mg/kg of MCT solution into rats. Two weeks later, the right ventricular systolic pressure rose to 25.4 ± 2.2 mmHg in the MCT group and to 13.3 ± 1.4 mmHg in the control group.…”
Section: Myocyte Investigationmentioning
confidence: 99%
“…The death rate from failing myocardium in the right ventricle as a result of MCT administration increases in a dose-dependent manner. [12][13][14][15][16][17] Hirota, et al 2) subcutaneously injected 40 mg/kg of MCT solution into rats. Two weeks later, the right ventricular systolic pressure rose to 25.4 ± 2.2 mmHg in the MCT group and to 13.3 ± 1.4 mmHg in the control group.…”
Section: Myocyte Investigationmentioning
confidence: 99%
“…19 Increased angiotensin-converting enzyme expression is observed in plexiform lesions in PAH, 20 and angiotensin-converting enzyme inhibition seems to delay pulmonary vascular neointimal formation. 21 Therefore, the renin-angiotensinaldosterone system (RAAS) represents a group of candidate genes that could modify disease severity and/or age at diagnosis of individuals predisposed to develop PAH. Angiotensin II (Ang II) binds primarily to the Ang II type-1 receptor (AT1R) to promote vascular smooth muscle constriction.…”
Section: Introductionmentioning
confidence: 99%
“…Previous investigators have reported that lung ACE activities were significantly decreased in monocrotaline-induced PH rats and have suggested that the reduction in lung ACE activity is a result rather than a cause of PH (25). However, ACE inhibitors have been shown to prevent monocrotaline-induced PH in rats (26,27), while the effects of ARBs in monocrotaline-induced PH rats have not yet been determined. Cassiss et al (28) reported that the ARB losartan failed to prevent monocrotaline-induced PH.…”
mentioning
confidence: 99%
“…Okada et al (26) compared an ACE inhibitor, quinapril, with losartan, and though both agents were found to prevent PH, the extent of inhibition with losartan was clearly weaker than with quinapril. From these results, they speculated that the mechanism of action of ACE inhibitors in PH might depend on the increase of bradykinin rather than on the reduction of angiotensin II formation (26,28). On the other hand, the ARB irbesartan was found to significantly prevent PH (29), just as our study showed that candesartan prevented PH.…”
mentioning
confidence: 99%